The Subversion of Victorian Morality in Bloodborne (2015) - SLAVEN LENDIĆ, (VIA PANORAMICA: Revista de Estudos Anglo-Americanos / A Journal of Anglo-American Studies, 2025)
This article examines how the Japanese gothic video game Bloodborne, consciously and intentionally, subverts the historical, ethical, and philosophical concept of Victorian morality. The article takes into account that the Victorian Compromise is an integral part of Victorian morality, and as such, it partly originates from deeply influential and far-reaching utilitarian philosophy (and politics) of English social reformer, jurist and philosopher Jeremy Bentham (1748 – 1832). Bloodborne subverts Victorian morality by presenting it as a stagnant, hypocritical, and plainly ineffective moral system that fails when the community faces a crisis or a state of exception. For further explanation on the state of exception, this article uses the framework presented by a relevant contemporary thinker of ethics and politics Giorgio Agamben (1942). Within Bloodborne and its setting, the gothic city of Yharnam, the state of exception is the Hunt. The Hunt is shown to be pushing the citizens and their views on civic responsibility, ethics, solidarity and critical reasoning to its breaking point. Instead of Bloodborne citizens being dismissed as simply cruel, selfish or ignorant, it should be recognized that their views are deeply influenced by the ideology of Victorian morality. The evidence for Victorian morality being a consciously present and significant underlying factor in the game is further reinforced by the omnipresent Victorian aesthetics and architecture, soundtrack, British accents in the English dub of the game, as well as numerous other factors. Bloodborne is therefore a Japanese interpretation and subversion of a deeply Western morality tradition.